1. DERMOSCOPY IN THE EVALUATION OF ONYCHOMYCOSIS (Vietnam Journal of Community Medicine, 2024)
Introduce: Onychomycosis represents all fungal infections of the nail including dermatophytes, yeast and mold. Dermoscope can help to identify multiform signs of onychomycosis effectively. Objectives: To characterize onychomycosis signs in the outpatient using bronchoscopy Materials and methods: 105 outpatients who were diagnosed with onychomycosis through direct microscopic examination with potassium hydroxide 20% and fungal culture from 8/2022 to 8/2023 in the National Hospital of Dermatology and Venereology participated in this study. Onychomycosis signs were characterized using a Fotofinder Dermoscope. Results: The main dermoscopic signs of 105 onychomycosis patients are cream-colored pigmented (97,5%), dry scales (95,1%), short spikes (81,9%), ruined appearance (65,7%), aurora borealis (63,8%) which had high sensitivity. Longitudinal striae and dermatophyte rates were 21,9 and 17,1%. Longitudinal striae occupied higher in the onychomycosis group caused by dermatophytes, but ruin appearance was higher in the yeast group. Clinical signs were more serious in the toenail than in the fingernail including serrated distal nail edge, aurora Borealis, longitudinal striae, onychoschizia and ruin appearance. Conclusion: Dermoscopy is useful for examining multiform clinical signs of onychomycosis
Keywords: Onychomycosis, ruin appearance, longitudinal striae, aurora borealis, spikes.